PENGARUH STRATEGI PEMBELAJARAN JIGSAW DAN PROBLEM BASED LEARNING TERHADAP SKOR KETERAMPILAN METAKOGNITIF SISWA PADA MATA PELAJARAN BIOLOGI - Aisyah, Siti; Ridlo, Saiful (Journal of Biology Education, 2015)
AbstractThe purposes of this study were to analyze the difference of studentâs metacognitive skill score between PBL class and Jigsaw class, analyze the difference of studentâs learning outcomes between PBL class and Jigsaw class,Â  and analyze the relationship between metacognitive skill score and learning outcomes. This was an experimental research. The population was 156 students in grade XI Science in State Senior High School 1 Pecangaan, Jepara academic year 2013/2014. Cluster random sampling technique was used and result two groups, namely PBL groupÂ  and Jigsaw group . The PBL groupÂ  was subjected to Problem Based Learning model, and the Jigsaw group was subjected to Jigsaw model. After learning, metacognitive skill score and learning outcomes of cognitive test performed in both groups PBL and Jigsaw to collect the data. The results showed that there was no differences average of metacognitive skill score between students in PBL class and Jigsaw class, there was differences of learning outcomes between students in PBL class and Jigsaw class, PBL class showed a higher learning outcomes significantly than Jigsaw class, there was a possitive strong relationship between metacognitive skill score and learning outcomes, and the percentage of students who reach the mastery learning in group subjected Problem Based Learning more than or equal to 75%, whereas in group subjected Jigsaw less than 75%.Â AbstrakPenelitian ini bertujuan untuk menganalisis perbedaan keterampilan metakognitif antara kelas PBL dan kelas Jigsaw, untuk menganalisis perbedaan hasil belajar kognitif antara kelas PBL dan kelas Jigsaw, dan menganalisis hubungan antara keterampilan metakognitif dengan hasil belajar kognitif. Penelitian ini merupakan penelitian eksperimen dengan populasi siswa kelas XI IPA SMA N 1 Pecangaan, Jepara tahun pelajaran 2013/2014. Pengambilan sampel dengan teknik cluster random sampling terpilih dua kelompok, yaitu kelompok kelas PBL dan kelompok kelas Jigsaw. Kelompok PBL dikenai pembelajaran model Problem Based Learning dan kelompok Jigsaw dikenai model pembelajaran model Jigsaw. Setelah dilakukan pembelajaran pada kedua kelompok dilakukan pengumpulan data dengan tes lembar inventori kesadaran metakognitif dan tes hasil belajar kognitif. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan rata-rata skor keterampilan metakognitif siswa antara kelas PBL dan kelas Jigsaw, terdapat perbedaan rata-rata hasil belajar kognitif siswa antara kelas PBL dan kelas Jigsaw, kelas PBL menunjukkan hasil belajar kognitif yang lebih tinggi secara signifikan dibanding kelas Jigsaw, adanya hubungan positif yang kuat antara skor keterampilan metakognitif dan hasil belajar kognitif, dan persentase siswa yang mencapai ketuntasan belajar pada kelompok yang menggunakan pembelajaran PBL lebih dari atau sama dengan 75%, sedangkan kelompok yang menggunakan pembelajaran Jigsaw kurang dari 75%.Â Â